The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1094/cm-2004-0628-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management in No-Tillage and Ridge-Tillage Systems Affects Short-Season Corn Grown on Claypan Soil

Abstract: Success of conservation tillage systems requires good fertilizer management, especially nitrogen applied to crops grown on claypan soils in the eastern Great Plains. Recently introduced, short‐season corn (Zea mays L.) hybrids, that mature earlier and potentially avoid drought problems common on these soils in late summer, provide producers with another viable cropping option. However, information on N management in conservation tillage systems is lacking for short‐season corn grown on claypan soils. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…If N deficiency occurs, stress at a specific point in the plant’s life cycle should have the greatest effect on the yield components determined at that specific growth stage. Specific corn grain yield components have been used for detailed assessments of effects associated with breeding programs, N management, and population stress (Iremiren and Milbourn, 1980; Karlen and Camp, 1985; Sweeney and Jardine, 2004; Van Roekel and Coulter, 2012; Ci et al, 2013, Mondo et al, 2013). Corn yield components contribute to grain yield as shown in Eq.…”
mentioning
confidence: 99%
“…If N deficiency occurs, stress at a specific point in the plant’s life cycle should have the greatest effect on the yield components determined at that specific growth stage. Specific corn grain yield components have been used for detailed assessments of effects associated with breeding programs, N management, and population stress (Iremiren and Milbourn, 1980; Karlen and Camp, 1985; Sweeney and Jardine, 2004; Van Roekel and Coulter, 2012; Ci et al, 2013, Mondo et al, 2013). Corn yield components contribute to grain yield as shown in Eq.…”
mentioning
confidence: 99%
“…2). Because the potential number of kernels per ear and ear size are generally determined at the V12 stage (Ritchie et al, 1993), greater early season N uptake by corn with ridge‐till than no‐till (V12) may partially explain greater yield and kernels per ear with ridge‐till, particularly in a higher yielding environment (Sweeney and Jardine, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The overall experiment was previously described in Sweeney and Jardine (2004) and is summarized here for the reader's benefit. The soil was a Zaar silty clay (fine, montmorillonitic, thermic Vertic Hapludoll) with approximately 30 cm of topsoil overlying a “claypan” B horizon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this appeared to be a result of a similar increase in the number of kernels per ear. Compared with no N fertilization, N applied at optimum levels can nearly double the number of kernels per ear (24). Across a range of N levels, correlation showed that as kernels per ear increased, the yield of multiple corn lines also increased (18).…”
Section: N-p Fertilizer Timing and Placement Effects On Corn Yield Anmentioning
confidence: 99%